New perspectives on narrative and multimodality [ - Page, Ruth , 1972- (Routledge studies in multimodality, 2009)
Investigates the diverse but integrated semiotic potential of storytelling. This collection provides an analysis of how narrative operates using combinations of visual, typographic, aural, gestural and haptic resources.